The influence of neurocognitive deficits on subjective quality of life in schizophrenic in-patients - Kopyciński, Zbigniew; Czernikiewicz, Andrzej (Current Problems of Psychiatry, 2012)
Cognitive deficits are an important dimension of schizophrenia. They are evident in the premorbid period and in the first episode of psychosis and they are moderate or marked. Cognitive deficits are closely linked with community outcome. The domains of quality of life reflect the patient´s difficulties such as side effects, lack of motivation, lack of social contacts and others. Theoretically neurocognitive deficits should interfere with the domains of quality of life of schizophrenic patients. The purpose of this paper was to review the literature and to present the results of our study. We tested hypothesis that cognitive deficits have direct negative impact on quality of life. The research was carried among 100 inpatients. The following instruments were used: The SQOL scale, the BPRS4 scale, the BNS scale, the Calgary scale and the Łucki Verbal Fluency Test as a measure of neurocognitive deficits. The correlations between measurable variables were carried with Spearman coefficient Rxy. In investigated group neurocognitive deficits weakly correlated only with motivation and energy domain of SQOL scale.